Complete transmural epicardial ablation reduces organized areas in atrial fibrillation. (25th November 2020) - Rogers, A; Ravi, N; Bhatia, N.K; Shah, R.L; Pong, T; Tung, J.S; Purewal, S; Baykaner, T; Rappel, W.J; Brodt, C.R; Wang, P.J; Lee, A; et al.
Abstract: Background: The surgical maze is suggested to be effective in persistent atrial fibrillation (AF) by reducing the area for fibrillatory wavelets. However, the mechanism for recurrence and next treatment steps are unclear. Purpose: We set out to evaluate the impact of complete transmural epicardial maze lesion sets on the extent atrial organization using novel analyses of wide-area recordings of AF. Methods: 19 patients (age 50.9±12.0, 78% male) underwent maze followed by endocardial mapping of AF with a 64-pole basket catheter. Block across roof, floor, and pulmonary vein lesions sets was assessed by high-density voltage mapping and organized zones of AF were assessed by panoramic recordings. Total organized area and mean area of the dominant site were evaluated using automated custom scripts. Results: Patients had 3.2±0.9 organized regions in 1 minute of LA recordings. A 54 yo F showed residual conduction to the posterior wall from the roof (purple, Fig. 1A) and a figure-of-8 propagation pattern during AF (arrows, fig B) which terminated with localized ablation (yellow lesions, Fig. 1A, red X, Fig. 1B). Overall, patients with complete block on epicardial lesion set had smaller areas of organization (13.7±8% vs. 45.7±32% of mapped areas, p=0.029) vs. those with gaps. The average size of the dominant area was smaller with complete transmural lines than with gaps (5.7±3% vs. 15.9±10%, p=0.033) (Fig. 1C). Conclusion: These results show that complete transmural lesion sets constrain the critical mass available for AF, with smaller resulting organized zones. Future studies that quantify how partitioning the atrial surface affects AF may help personalize lesion sets after maze. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): NIH NRSA F32 United States